Risk management to prevent medication errors among the Outpatient Department in Khaowong Hospital, Kalasin Province - Yatpramot, Warunya; Leethongdee, Songkramchai; Chualinfa, Sangud (UBRU Journal for Public Health Research, 2020)
The purpose of this action research was to develop a model for risk management to prevent medication errors in the Outpatient Department in Khaowong Hospital, Kalasin Province. Participants were selected from a random criteria of 20 people. Data was collected both quantitative and qualitative. By a questionnaire, interview, focus group and recording form. Quantitative data was analyzed using by descriptive statistics and inferential statistics included nonparametric (Wilcoxon Signed-Ranks Tests). Qualitative analyzed by content. The research found that the development of this model had 10 stages: 1) Study from problems and context, 2) Survey knowledge and practice, 3) Problems analysis, 4) Participation workshop for an action plan, 5) Develop safe from using medication systems, 6) Develop safe from look-alike sound-alike medication names systems, 7) Develop risk management systems, 8) Participate observers and supervision, 9) Evaluation and 10) Knowledge exchange and lessons learned. The resulting showed score of knowledge and practice standards were increased more than before the operation at statistical significance of .05. The incidence of outpatient medication errors has decreased from 10.85 to 9.82 times per 1,000 prescriptions. Resulting in the development of a risk management system of medication use of the Khaowong Hospital called the K-W-S-C model. In conclusion, the key success factors comprised: Participation of teams. Approach information and knowledge to apply systematically. Conduct with intention policy support from the leaders and promote a patient safety culture.